1999
DOI: 10.1598/rrq.34.1.2
|View full text |Cite
|
Sign up to set email alerts
|

What Johnny Likes to Read Is Hard to Find in School

Abstract: S Research about the importance of interest in learning suggests that students who have access to materials of interest are more likely to read and thus to improve their reading achievement and attitudes. This study examined the reading preferences and access to reading materials of sixth‐grade students from three middle schools in a large ethnically and economically diverse southwestern U.S. school district. Preference surveys and open‐ended questions about favorite materials and authors showed that the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
134
1
14

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(156 citation statements)
references
References 21 publications
7
134
1
14
Order By: Relevance
“…Ils abordaient des thèmes scientifiques ou sociaux qui soutenaient l'intérêt des élèves (par exemple une forêt sous-marine de 52 000 ans, l'invention de la gomme à mâcher, les courses extrêmes, une imprimante à pizza, etc.). Entre 10 et 14 ans, les élèves apprécient les textes qui décrivent des expériences étonnantes (Guthrie & Davis, 2003), qui proviennent de magazines ou de sites web s'adressant aux jeunes et traitant de thèmes actuels (Worthy, Moorman & Turner, 1999). De tels textes suscitent l'engagement affectif et cognitif des jeunes lecteurs (McRae & Guthrie, 2009).…”
Section: Déroulement De L'interventionunclassified
“…Ils abordaient des thèmes scientifiques ou sociaux qui soutenaient l'intérêt des élèves (par exemple une forêt sous-marine de 52 000 ans, l'invention de la gomme à mâcher, les courses extrêmes, une imprimante à pizza, etc.). Entre 10 et 14 ans, les élèves apprécient les textes qui décrivent des expériences étonnantes (Guthrie & Davis, 2003), qui proviennent de magazines ou de sites web s'adressant aux jeunes et traitant de thèmes actuels (Worthy, Moorman & Turner, 1999). De tels textes suscitent l'engagement affectif et cognitif des jeunes lecteurs (McRae & Guthrie, 2009).…”
Section: Déroulement De L'interventionunclassified
“…For example, the study conducted by Worthy (1999) addressed the reading preferences of elementary school students. It revealed that the students of grade-6 preferred to read story books, cartoons, comics, popular magazines, and sports even though these books were rarely available in school libraries.…”
Section: Review Of Related Studiesmentioning
confidence: 99%
“…During the RT"s weekly visits to the schools, the RTs read with individual boys for a period of 30 minutes. The texts used with each child were consistent across groups, and were based on research about books that hold high interest for some boys (Worthy, Moorman, & Turner, 1999). Some books were read from printed texts and others were read in pdf.…”
Section: Procedures and Instrumentsmentioning
confidence: 99%